2010
DOI: 10.1021/jp106098z
|View full text |Cite
|
Sign up to set email alerts
|

CuO Nanosheets for Sensitive and Selective Determination of H2S with High Recovery Ability

Abstract: In this article, cupric oxide (CuO) leafletlike nanosheets have been synthesized by a facile, low-cost, and surfactant-free method, and they have further been successfully developed for sensitive and selective determination of hydrogen sulfide (H 2 S) with high recovery ability. The experimental results have revealed that the sensitivity and recovery time of the present H 2 S gas sensor are strongly dependent on the working temperature. The best H 2 S sensing performance has been achieved with a low detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
95
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(99 citation statements)
references
References 49 publications
3
95
0
1
Order By: Relevance
“…Again, the sensing mechanism of this reducing gas was explained by the interaction with the oxygen species at the CuO surface. Water and sulphur dioxide were identified as the main resulting products [7],…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, the sensing mechanism of this reducing gas was explained by the interaction with the oxygen species at the CuO surface. Water and sulphur dioxide were identified as the main resulting products [7],…”
Section: Resultsmentioning
confidence: 99%
“…In this latter application, films of CuO were reported to detect O 3 , CO and C 5 H 2 OH among other chemical species [7][8][9]. Recently, the potential of CuO nanowires as building-blocks of new devices has been pointed out [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Several groups had studied on CuO nanowires-based gas sensors, such as H 2 S sensor [9], [10], [13], humidity sensor [6], [12], but those sensors are based on CuO nanowires arrays and they still work at high temperature. Here our single CuO nanowire alcohol sensor can work at room temperature.…”
Section: B Single Cuo Nanowire Alcohol Sensormentioning
confidence: 99%
“…When the single CuO nanowire is exposed to N 2 again, the current recovers to nearly its initial value. Compared to the nanowires arrays based sensors working only at high temperature [6], [9], [10], [12], [13], the single nanowire alcohol sensor can work at room temperature with the reasons probably as follows. In those sensors based on nanowires arrays, the CuO nanowires are protruded from relatively thick CuO substrate through which the detected current passes.…”
Section: B Single Cuo Nanowire Alcohol Sensormentioning
confidence: 99%
“…It has been shown that CuO can be used in high temperature superconductors, magnetic storage media, gas sensor, field emitters and heterogeneous catalysis, and so on [4]. The CuO nanowires based sensors can take advantage of testing many objects, such as NO 2 [5], H 2 S [6], pH [7], humidity [8], glucose [9], etc.…”
Section: Introductionmentioning
confidence: 99%